THE IMPLICATIONS OF FREE TRADE AREA ON DOMESTIC INDUSTRIES: EMPIRICAL EVIDENCE FROM NIGERIA (Journal of Economics and Sustainability, 2022)
The paper sought to examine the impact of Free Trade Area on Nigeria’s domestic industries from 1980 to 2019. It employed the autoregressive distributive lag (ARDL) estimation technique to analyze the short-run and long-run relationships between the independent and the explanatory variables, thereby validating the objective of the study. All the variables were stationary after the first difference, except Ease of Doing Business (EDB). In the short run, all the explanatory variables were statistically significant after two-period lags. However, in the long run, the estimated ARDL results revealed all the explanatory variables were negatively related to the industrial growth in the Nigerian economy. Such a negative relationship between Free Trade Area (FTA) as captured by trade openness and growth of the industrial output will portend a deleterious consequence on the industrial sector of the Nigerian economy. By implication, when fully consummated with the dearth of trade infrastructure coupled with a lack of competitive network structures, Free Trade Area will ensure that the industrial sector in Nigeria becomes manifestly dependent on imported goods produced from low-cost production centres in Africa. Based on this conclusion, it is recommended that a cautious and guided opening of the Nigerian economy should be the operational template between Nigeria and the rest of Africa in terms of the Africa Continental Free Trade Area (AfCFTA).